The effects of human and organizational factors on students’ communication skill development - Rodzalan, Shazaitul Azreen; Mohamed Saat, Maisarah (Institute of Interdisciplinary Business Research, 2013)
This conceptual paper review the underpinning theory and past literatures on communication skill with industrial training intervention. The paper intends to investigate the effect of human and organizational factors on students’ communication skill development using pre and post industrial training approach. It proposes that students demographic and motivation (human factors), as well as supervisor, demographic, duration, job scope and culture (organizational factors) may influence students’ communication skill. Subsequently, a number of hypotheses and a framework of communications skill development are proposed in identifying if any development occurs before and after students in higher education institutions attended the industrial training. This paper also illustrates the methodology used and finalized with conclusions.